The principle of causality and the coordination of concepts and spatio-temporal objects in cassirer's philosophy - Pringe, Hernan Bruno (2014)
This paper analyzes the role of the principle of causality in Cassirer's account of the coordination of concepts and spatio-temporal objects. We shall see that, in contradistinction to Kantian schematism, Cassirer maintains that this coordination is not achieved by means of a third element (the schema), which albeit intellectual is nevertheless also sensible. Rather, in Cassirer's view, the coordination will take place through a specification of the concepts that should be sought "within the domain of concepts itself." We shall show that the principle of causality is the ultimate condition upon which the possibility of the coordination of concepts and spatio-temporal objects depends.